2021
DOI: 10.52417/ajhse.v2i2.164
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Composition and Proximate Analysis of Poultry Feeds Sold in Benin City, Nigeria

Abstract: Poultry farming contributes significantly to poverty alleviation by providing employment opportunities to Nigerians. Feed quality is the most prominent challenge of the poultry sector. This study was aimed at assessing the fungal and proximate qualities of poultry feeds sold in Benin City, Nigeria. Poultry feed samples (starter, grower and finisher) were obtained from five stores in Benin City. Enumeration and isolation of fungi was carried out using the spread plate method on potato dextrose agar and Aspergil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
2
1
Order By: Relevance
“…Aspergillus flavus and Aspergillus niger were isolated from 100% of the compounded feeds in this study, making them the most predominant species in the samples. This is in line with the findings of [12,13] who reported A. flavus and A. niger as the most predominant species isolated from poultry feeds southwest Nigeria and Iran respectively. Similarly, the results of this study are also in consonance with the work of [14,15] Pakistan and [16] Brazil who reported A. flavus and A. niger as predominant species contaminating poultry feeds whereas the study by [10] describe only Aspergillus niger as the most frequently isolated species in feed samples and ingredients.…”
Section: Discussionsupporting
confidence: 92%
“…Aspergillus flavus and Aspergillus niger were isolated from 100% of the compounded feeds in this study, making them the most predominant species in the samples. This is in line with the findings of [12,13] who reported A. flavus and A. niger as the most predominant species isolated from poultry feeds southwest Nigeria and Iran respectively. Similarly, the results of this study are also in consonance with the work of [14,15] Pakistan and [16] Brazil who reported A. flavus and A. niger as predominant species contaminating poultry feeds whereas the study by [10] describe only Aspergillus niger as the most frequently isolated species in feed samples and ingredients.…”
Section: Discussionsupporting
confidence: 92%
“…The crude fibre content (% dry weight) in the different feed brands ranged between 3.57 ± 0.11 -14.77 ± 0.14 % (Figure 4). The present result is higher than 3.53 ± 0.04 -8.45 ± 0.16 %, 5.27 -10.39 %, 4.3 -9.0 % and 2.89 -6.60 % crude fibre contents published in Ogbebor et al (2021), Ojabo and Wunduga (2020), Okafor and Ezebuo (2014) and Vakili et al (2015) respectively whereas 3.41 ± 0.17 -15.90 ± 6.46 % and 1.70 -38.75 % observed in Bukar and Saeed (2014) and Bukar and Saeed (2015) respectively were higher crude fibre contents. The mean values of the starter, grower and finisher rations of the feed brands exceeded the SON (2018) crude fibre maximum recommended limit of 5.00 %, 7.00 % and 5.00 % respectively except the layer ration (Figure 4).…”
Section: Igwemmar N C; Kolawole S A; Omoniyi a O; Bwai D M; Fagbohun ...contrasting
confidence: 78%
“…95 -20.47 ± 12.67 %, 6.84 -35.56 % and 5.46 -22.06 % respectively. On the contrary, Dewa and Tikau (2019), Hasan et al (2022), Ogbebor et al (2021), Ojabo and Wunduga (2020), Okafor and Ezebuo (2014) and Vakili et al (2015) obtained lower ash contents in poultry feeds than the present study ranging from 8.05 ± 0.57 -12.28 ± 0.41 %, 8.81 ± 0.03 -8.97 ± 0.05 %, 3.69 ± 0.32 -4.99 ± 0.33 %, 7.31 -12.76 %, 1.90 -2.00 % and 4.01 -6.70 % respectively. In a study by Ofori et al (2006), it was reported that low ash content of the feed pre-disposes birds to diseases and poor egg shell formation.…”
Section: Igwemmar N C; Kolawole S A; Omoniyi a O; Bwai D M; Fagbohun ...mentioning
confidence: 98%
See 1 more Smart Citation